LA COMUNICACIÓN EN LA AGENDA MEDIÁTICA DE LOS NEGOCIOS EN ESPAÑA - Enrique ARMENDÁRIZ (Fonseca, Journal of Communication, 2023)
This study analyzes the image projected by the Communication as a professional discipline and economic activity in the Spanish financial press. The analysis allows to know the issues that most often appear in the media discourse related to this field and the several specialized activities related, and explores the most important trends affecting their development. In this sense, it is a kind of picture of what the Communication sector is at present and want to become in the future, conducted from the perspective of agenda-setting.